Contributions of Christian Scholars in Tamil Literature: தமிழ் இலக்கிய வளர்ச்சியில் கிறித்தவத்தின் பங்கு - L John Silvia Prema, (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2021)
As early as 14th century, there have been continuous connections were established between the European nations and Indian sub-continent in the name of spreading the trinity concepts of Glory-Gold-Gospel. Several Christian Missionaries have reached India from Europe in order to wide-spread the Christianity. The learned and well-trained missionary personals chose to learn the local languages as soon as they reached to ease their activities. As a result of this, they indulged with the beauty of the Tamil language and its literary heritage. Soon, they became profound use of the language. In return, they also have made significant contributions to the development of the language and literature. It is well-known fact that one of them was the printing mechanism, which have paved ways for easier and fast printing in high volume than before. As a result of this, there were many books published with introduction of new Tamil font system, covering many genres like Prose, Modern Literature, Grammar, Inscription, Translation, Linguists, Dictionary and on. Along this, there have been so many poems were written and introduced into Tamil by Christian Poets as well. This article is aimed at studying such not well-discussed literatures within the Christian Literature domain. ஐரோப்பியர்கள் கிறித்துவ மதத்தைப் பரப்பவதற்குத் தமிழகத்திற்கு வந்தனர். அவர்கள் தமிழ் மொழியை இலக்கணப் பிழையின்றி ஆர்வத்தோடு கற்றுத் தேர்ந்தனர். தமிழின் இனிமையை உணர்ந்து தமிழ்மொழியைக் கொண்டாடினர். தமிழில் பல நூல்களை இயற்றியும் அதை அச்சு இயந்திரம் கொண்டு அச்சடித்துக் கொடுத்தனர். ஆசிய அளவில் முதன் முதலில் அச்சில் ஏற்றப்பட்ட மொழி தமிழ் மொழியாகும். ஐரோப்பியர்களின் தொண்டு அளவிடமுடியாதது. தமிழில் எழுத்துச் சீர்த்திருத்தம், உரைநடை, அகராதி, கல்வெட்டுகளை மொழிப்பெயர்த்தல் ஆகியவற்றைப் சீர்த்திருத்தம் செய்து தமிழ்மொழிக்குத் தொண்டாற்றினர். இவர்களைப் பின்பற்றி, தமிழ் அறிஞர்களும் தமிழ்மொழிக்குப் பல இலக்கியங்களைத் தொண்டாற்றியுள்ளனர். அவர்களுள் பெரிதும் அறிமுகமில்லாத கவிஞர்கள் பற்றியும் அவர்கள் ஆற்றிய பணிகள் குறித்து இங்கு காணலாம்.